Pengaruh Permainan Puzzle terhadap Motorik Halus Anak Usia 5-6 Tahun - Zahira Auladina Solihah; Lutfi Nur; Risbon Sianturi (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
This study investigates the effect of puzzle games on the fine motor skills of children aged 5–6 years. Although puzzles have frequently been used as educational media, empirical evidence comparing their effectiveness with conventional learning through a quasi-experimental design in Indonesian early childhood education remains limited. This research addresses this gap by examining the effectiveness of puzzle-based learning in improving children's fine motor development. A quasi-experimental study with a nonequivalent pretest-posttest control group design was conducted involving 20 children aged 5–6 years at TK PGRI Cibeureum, consisting of 10 children in the experimental group and 10 in the control group. Data were collected through observation using fine motor skill assessment instruments and analyzed using descriptive and inferential statistical techniques by comparing pretest and posttest scores between groups. The findings revealed that the experimental group achieved higher improvement than the control group, with mean scores increasing from 27.70 to 40.40, while the control group increased from 26.10 to 34.80. These findings demonstrate that puzzle games significantly enhance children's fine motor skills by improving hand-eye coordination, finger dexterity, concentration, and problem-solving abilities. This study contributes theoretically by strengthening evidence on play-based learning for fine motor development and practically recommends integrating puzzle games into early childhood learning activities to provide meaningful and developmentally appropriate stimulation